Characterization and oxygen binding properties of des-Arg human hemoglobin - Tosqui, P. [UNESP]; Bonini-Domingos, C.R. [UNESP]; Colombo, M.F. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2009)
The role of chloride in the stabilization of the deoxy conformation of hemoglobin (Hb), the low oxygen affinity state, has been studied in order to identify the nature of this binding. Previous studies have shown that arginines 141α could be involved in the binding of this ion to the protein. Thus, des-Arg Hb, human hemoglobin modified by removal of the α-chain C-terminal residue Arg141α, is a possible model for studies of these interactions. The loss of Arg141α and all the salt bridges in which it participates is associated with subtle structural perturbations of the α-chains, which include an increase in the conformational flexibility and further shift to the oxy state, increasing oxygen affinity. Thus, this Hb has been the target of many studies of structural and functional behavior along with medical applications. In the present study, we describe the biochemical characterization of des-Arg Hb by electrophoresis, high-performance liquid chromatography and mass spectroscopy. The effects of chloride binding on the oxygen affinity and on the cooperativity to des-Arg Hb and to native human hemoglobin, HbA, were measured and compared. We confirm that des-Arg Hb presents high oxygen affinity and low cooperativity in the presence of bound chloride and show that the binding of chloride to des-Arg does not change its functional characteristics as observed with HbA. These results indicate that Arg141α may be involved in the chloride effect on Hb oxygenation. Moreover, they show that these residues contribute to lower Hb oxygen affinity to a level compatible with its biological function.
Keywords: des-Arg hemoglobin; Oxygen affinity